Foreign Body Ingestion in an Adult not Associated with Mental Disorder: An Unusual Clinical Case Report - Dadá, Mahomed Sidique Abdul Cadar; Dadá, Abdul Habib Mahomed; Dadá, Zulaikhah Mahomed Sidique (Brazilian Journal of Case Reports, 2023)
Introduction and objective: Esophagus is a muscular and mucosal tubular organ with 4 physiological narrowing’s that are preferred sites for the retention of foreign bodies accidentally or deliberately ingested. The latter form is frequent in people with mental disorders and prisoners. The aim of this study is to describe a rare clinical case of foreign body ingestion.Case Report: This case describes an incident in which a young man deliberately swallowed a key to hide evidence of theft. This is a unique case in the literature of deliberate ingestion in mentally healthy people and not part of the prison population. Discussion: Foreign bodies are a public health problem, related with huge ENT doctor’s activities. It represents the first cause of ENT emergency services care. Although large foreign body ingestion is rare. The worldwide literature is full of articles related with little accidental foreign bodies ingestion, especially in children, such as coins, toys, fish bones and bones Conclusions: In the presence of intentionally and/or accidental foreign bodies ingested in adults, it is necessary to discard mental disorders or social factors.